2021
DOI: 10.1371/journal.pone.0257025
|View full text |Cite
|
Sign up to set email alerts
|

Use of pharmacotherapy for alcohol use disorder in Manitoba, Canada: A whole-population cohort study

Abstract: Objective Update the evidence on use of pharmacotherapy for alcohol use disorder in a Canadian population. Methods Using whole-population administrative data from Manitoba, Canada, we identified all residents age 12+ who were first diagnosed with alcohol use disorder between April 1, 1996 and March 31, 2015, and compared characteristics of those who filled a prescription for naltrexone, acamprosate or disulfiram at least once during that period to those who did not fill a prescription for an alcohol use diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
(47 reference statements)
0
17
0
1
Order By: Relevance
“…All this research, including corroborating international reports, has generated substantial interest in monitoring national trends in alcohol-related hospitalizations and developing strategies to reduce the risk of postdischarge harm and recurrent health service use. However, much of this work amalgamates everyone who experiences an alcohol-related hospitalization into a single cohort of individuals with a presumed AUD . In turn, there has been relatively little focus on the clinical diversity that exists within this population or if certain subgroups merit prioritization in efforts to reduce the risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All this research, including corroborating international reports, has generated substantial interest in monitoring national trends in alcohol-related hospitalizations and developing strategies to reduce the risk of postdischarge harm and recurrent health service use. However, much of this work amalgamates everyone who experiences an alcohol-related hospitalization into a single cohort of individuals with a presumed AUD . In turn, there has been relatively little focus on the clinical diversity that exists within this population or if certain subgroups merit prioritization in efforts to reduce the risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although our analyses are exploratory and did not identify causal factors underlying frequent ED visits, we hypothesize that recurrent ED visits by our patient cohort may suggest gaps in access to evidence-based substance use disorder management and mental health care in EDs and communities [ 47 ], particularly for the “extreme” subgroup. For instance, patients may present to EDs when their substance use-related needs are not met elsewhere, such as when primary care physicians are uncomfortable with substance use management and/or unable to liaise with addiction specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Urban and rural areas receive vastly different levels of treatment for alcohol use disorders, particularly when it comes to evidence-based care. A Canadian study found that family doctors and psychiatrists in urban areas were the primary prescribers of pharmacological treatments for alcohol use disorder, such as naltrexone, acamprosate, and disulfiram [34 ▪ ]. If a person resided in an urban area as opposed to a rural one, they were more likely to fill a prescription for medication for alcohol use disorder [34 ▪ ].…”
Section: Treatment Hospitalizations and Mortalitymentioning
confidence: 99%
“…A Canadian study found that family doctors and psychiatrists in urban areas were the primary prescribers of pharmacological treatments for alcohol use disorder, such as naltrexone, acamprosate, and disulfiram [34 ▪ ]. If a person resided in an urban area as opposed to a rural one, they were more likely to fill a prescription for medication for alcohol use disorder [34 ▪ ]. However, the treatment rates are very low.…”
Section: Treatment Hospitalizations and Mortalitymentioning
confidence: 99%